Using citizen science as a research prioritization tool to detect co‐occurrences of the invasive species Harmonia axyridis - Baudino, Florencia (2025)
1. Invasive species impact native ecosystems through associations with local biota;however, these co-occurrences and potential interactions remain poorly understood,particularly for small organisms like insects. Citizen science provides a valuabletool, providing broad spatial and temporal coverage to facilitate theobservation of species co-occurrences.2. Our aim was, using citizen science records, to detect co-occurrences and potentialnovel interactions between the invasive ladybird Harmonia axyridis and local biota(plants, arthropods and fungi) in Argentina.3. Over 50% of the photos showed H. axyridis in association with another species,mainly from the plant families Asteraceae, Rosaceae and Lamiaceae and the arthropodfamilies Aphididae and Coccinellidae. In addition, we report potential novelinteractions including predation, parasitism, interspecific mating and mixed aggregationswith local biota that have not been previously documented in Argentina, providingnew insights into possible ecological impacts of this invasive ladybird.4. Our findings highlight how citizen science can be used as a research prioritizationtool for invasive species research, revealing species co-occurrences and also uncoveringpotential novel interactions between invasive species and local taxa acrosslarge spatial and temporal scales.